2015
DOI: 10.14205/2310-9386.2015.03.01.1
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Effectiveness of Medical Therapy in Benign Prostatic Hyperplasia Patients in HUSM

Abstract: Introduction: Benign prostate hyperplasia (BPH), a progressive disease, can cause various urinary complications if left untreated. Aims and Objective: The current study was desigined to compare international prostate symptom score (IPSS), urine flow rate (Qmax), Prostate specific antigen (PSA) in pre and post treatment among patients with Benign prostate hyperplasia and to asses their quality of life. Methodology: A cross sectional study was designed at Hospital Universiti Sains Malaysia, including all patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Of the infected persons, 13.3% were still infectious, and these were all women from the Kabyè-tem ethnic group. Our findings corroborate the results of a previous study that observed that the regions of highest HBsAg seroprevalence among 15–24 years old individuals were the central region (27.7%) and the Kara region (23.1%), which are inhabited by the Kabyè-tem [9]. This ethnic group is the second largest in Togo.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Of the infected persons, 13.3% were still infectious, and these were all women from the Kabyè-tem ethnic group. Our findings corroborate the results of a previous study that observed that the regions of highest HBsAg seroprevalence among 15–24 years old individuals were the central region (27.7%) and the Kara region (23.1%), which are inhabited by the Kabyè-tem [9]. This ethnic group is the second largest in Togo.…”
Section: Discussionsupporting
confidence: 91%
“…In the hospital-based Lomé study and the national survey among people aged 15 to 24 years there was a statistically significant difference in the prevalence of HBsAg between the two genders [9, 10]. This discrepancy may be due to our smaller sample size.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation